Religious Integration with Science Education Concept in The Era of The Rise of Artificial Intelligence - A'yun, Kurroti (Faculty of Teacher Training and Education, Universitas Terbuka, 2024)
The progress of the times is marked by the intensive use of advanced technology in various fields, especially using artificial intelligence in various lines of life, such as education, health, games for the younger generation, and so on. The strength of faith and piety is really needed in this type of life pattern so that life is not wasted and there is no damage on the face of the earth. Therefore, it is necessary to discuss the integration of faith and piety in facing the emergence and rise of artificial intelligence (AI), especially in the world of education, so that the young generation who will be the successors of life in the future is not eroded by the flow of artificial intelligence and eliminates the inner intelligence regarding the existence of beliefs. that goodness from God is truly true goodness. The author has made quantitative observations of several young people at the high school level, both private and public. The results show that there are differences in attitudes and behavior in facing the rise of artificial intelligence, especially in the world of education. In this research, it was found that the young generation at high school level who were introduced to faith and piety more intensely, had different attitudes and behavior in dealing with life's problems, but there was a tendency to have an understanding of the concept of life as a servant of God.